2010
DOI: 10.1088/0004-637x/723/2/1583
|View full text |Cite
|
Sign up to set email alerts
|

A Precise Asteroseismic Age and Radius for the Evolved Sun-Like Star Kic 11026764

Abstract: The primary science goal of the Kepler Mission is to provide a census of exoplanets in the solar neighborhood, including the identification and characterization of habitable Earth-like planets. The asteroseismic capabilities of the mission are being used to determine precise radii and ages for the target stars from their solar-like oscillations. Chaplin et al. (2010) published observations of three bright G-type stars, which were monitored during the first 33.5 d of science operations. One of these stars, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 100 publications
3
118
0
Order By: Relevance
“…This demonstrates that seismic observations of subgiants have the potential to contribute to ongoing debates, such as the question of the amount of core overshooting, the efficiency of convection, and the abundances of heavy elements in stars. This is all the more exciting because the space mission Kepler has claimed the detection of = 1 avoided crossings in several targets (Chaplin et al 2010;Metcalfe et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrates that seismic observations of subgiants have the potential to contribute to ongoing debates, such as the question of the amount of core overshooting, the efficiency of convection, and the abundances of heavy elements in stars. This is all the more exciting because the space mission Kepler has claimed the detection of = 1 avoided crossings in several targets (Chaplin et al 2010;Metcalfe et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…To obtain an asteroseismic estimate of the stellar mass and radius we employed the code Catania-GARSTEC (Bonanno et al 2002b), following the approach and the physical input described in Metcalfe et al (2010) for KIC 11026764. In our grid model search we considered the average values from ROTFIT and Bruntt et al (2012) as astrophysical constraints, and the large separation Δν = 49.6 μHz (Appourchaux et al 2012) as the main asteroseismic constraint.…”
Section: Observations Of Kic 5955122mentioning
confidence: 99%
“…Stello et al 2013Stello et al , 2015Chaplin et al 2015). These data allow us to determine accurate stellar properties that help to constrain stellar evolution models (Metcalfe et al 2010;Mathur et al 2012) and improve the determination of the properties of the exoplanets they might host (Guillot & Havel 2011;Huber et al 2013). A review of the progress with Kepler in the field of the red giant stars can be found in Christensen-Dalsgaard (2012) and García & Stello (2015).…”
Section: Introductionmentioning
confidence: 99%